PENERAPAN PENDEKATAN KONSTRUKTIVISME BERBANTUAN MEDIA ICT UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SMA PADA MATA PELAJARAN EKONOMI: PENERAPAN PENDEKATAN KONSTRUKTIVISME BERBANTUAN MEDIA ICT UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA SMA PADA MATA PELAJARAN EKONOMI - Vebrina, Dinda; Bongsu, Halim; Oktaviana, Nur; Mega Sari, Asti; Sari Ritonga, Puspa; Adiani Harahap, Siti; Fauzi Pulungan, Ahmad; Aprilda, Elsa; Hannum, Saidah; Holijah, Siti; Tanjung, Maya; Tamba, Marisitua; Harahap, Adawiyah; Siregar, Dedi; Hasibuan, Wenni; Srikandi; Syahputra, Ramadan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to examine the effect of a constructivist approach assisted by Information and Communication Technology (ICT) media on students’ learning independence in economics subjects at SMA Negeri 1 Angkola Selatan. This research employed a quantitative approach using a quasi-experimental design with a pretest–posttest control group. The subjects consisted of 60 tenth-grade students, divided into an experimental group and a control group. Data were collected using a learning independence questionnaire and analyzed using normality, homogeneity, and t-tests. The results show a significant difference in learning independence between students taught using the constructivist approach assisted by ICT media and those taught using conventional learning. Students in the experimental group experienced a higher improvement in learning independence across all indicators, including learning planning, learning process management, monitoring learning progress, and self-evaluation. It can be concluded that the constructivist approach assisted by ICT media has a positive and significant effect on improving students’ learning independence in economics learning.